Develop telescope wing of UAV - Ng, Yeunn Ject. (2010)
This project involves the design and fabrication of a working prototype of the telescopic wing for an Unmanned Aerial Vehicle (UAV). Simulation showed that the wing is able to extend and retract span wise from centre wing box.